Strategi Pemasaran Efektif Untuk Meningkatkan Penjualan di Era Digital - Nurul Indawati; Bambang Setyo Pambudi (MES Bogor, 2024)
This study aims to analyze effective marketing strategies for increasing sales in the digital era based on literature review and to identify challenges and solutions in implementing digital marketing strategies. The research employs a literature study approach, with primary data sourced from books, scientific journals, theses, dissertations, e-books, and other written materials. The findings indicate that effective digital marketing strategies include the utilization of social media, email marketing, SEO, product diversification, and e-commerce to reach a broader audience and boost sales. Common challenges include limited resources, lack of technology training, and shifts in consumer behavior. Proposed solutions involve intensive training, creative content management, the use of advanced technologies such as Artificial Neural Networks, as well as optimizing social media and user-generated content. Thus, digital marketing strategies can be a powerful tool for enhancing a company's competitiveness in the digital era, provided the existing challenges are effectively addressed